Australia's National Notifiable Diseases Surveillance System 1991–2011: expanding, adapting and improving. Issue 5 (9th January 2017) - GIBNEY, K. B.; CHENG, A. C.; HALL, R.; LEDER, K.
SUMMARY: We reviewed key attributes (flexibility, data quality and timeliness) of Australia's National Notifiable Diseases Surveillance System (NNDSS) over its first 21 years. Cases notified to NNDSS from 1991 to 2011 were examined by jurisdiction (six states and two territories) and sub-period to describe changes in the number of notifiable diseases, proportion of cases diagnosed using PCR tests, data quality (focusing on data completeness), and notification delays. The number of notifiable diseases increased from 37 to 65. The proportion of cases diagnosed by PCR increased from 1% (1991–1997) to 49% (2005–2011). Indigenous status was complete for only 44% notifications (jurisdictional range 19–87%). Vaccination status was complete for 62% (jurisdictional range 32–100%) and country of acquisition for 24% of relevant cases. Data completeness improved over the study period with the exception of onset date. Median time to notification was 8 days (interquartile range 4–17 days, jurisdictional range 5–15 days); this decreased from 11 days (1991–1997) to 5 days (2005–2011). NNDSS expanded during the study period. Data completeness and timeliness improved, likely related to mandatory laboratory reporting and electronic data transfer. A nationally integrated electronic surveillance system, including electronic laboratory reporting, would further improve infectious disease surveillance in Australia.